Urinary lithiasis and urinary tract malformations in children: A retrospective study of 34 cases - Jamila Chahed; Riadh Jouini; Imed Krichene; Kaies Maazoun; Mohamed Ben Brahim; Abdellatif Nouri (Wolters Kluwer Medknow Publications, 2011)
Background: Although the association of urinary lithiasis and urinary tract malformation is not rare, their management poses challenges. The aim of this study was to evaluate the relationship between urolithiasis and malformations of the urinary system. There were 34 patients (19 males and 15 females) with a mean age of 4.8 years (range, 2 months to 14 years). All patients had urinary lithiasis with a urinary tract malformation. Abdominal pain was the most frequent clinical symptom (38%). Urinary infection was found in 7 patients (21%) and macroscopic haematuria was present in 10 patients (29%). The most frequent urinary tract malformations were megaureter (8 cases), uretero-pelvic junction obstruction (7 cases) and vesico-ureteric reflux (8 cases), but its malformative origin could not be confirmed. Treatment consisted of lithiasis extraction in 32 cases associated with specific treatment of the uropathy in 27 cases. Postoperative outcome was uneventful in all cases. In fact, urinary lithiasis and urinary tract malformation association is not rare. Indeed, 9-34% of urinary lithiasis are noted to be associated with urinary tract malformation. Positive diagnosis relies specifically on kidney ultrasound, intravenous urography, and urethrocystography. Treatment depends on the type of urinary tract malformation, localisation and size of the urinary lithiasis. Conclusion: In conclusion, urinary lithiasis and urinary tract malformation association is a frequent eventuality. Surgical intervention is the usual mode of treatment.